Pleckstrin Homology Domain Interacting Protein (PHIP); A Target Enabling Package - Brennan, P (University of Oxford, 2018)
A description of the materials and methods is included within the TEP datasheet. SGC Oxford has expressed, purified and crystallized the second bromodomain of PHIP as part of the probe programme. Fragment screening and X-ray crystallography identified binders, some of which optimised to uM affinity. However, molecules with probe properties were not obtained. Consequently it has been decided to put the information generated into the public domain.